Separation of methane from different gas mixtures using modified silicon carbide nanosheet: Micro and macro scale numerical studies - Bayat, Golchehreh; Saghatchi, Roozbeh; Azamat, Jafar; Khataee, Alireza (Chinese journal of chemical engineering, 2020)
This research discusses the separation of methane gas from three different gas mixtures, CH4/H2S, CH4/N2 and CH4/CO2, using a modified silicon carbide nanosheet (SiCNS) membrane using both molecular dynamics (MD) and computational fluid dynamics (CFD) methods. The research examines the effects of different structures of the SiCNSs on the separation of these gas mixtures. Various parameters including the potential of the mean force, separation factor, permeation rate, selectivity and diffusivity are discussed in detail. Our MD simulations showed that the separation of CH4/H2S, and CH4/CO2 mixtures was successful, while simulation demonstrated a poor result for the CH4/N2 mixture. The effect of temperature on the diffusivity of gas is also discussed, and a correlation is introduced for diffusivity as a function of temperature. The evaluated value for diffusivity is then used in the CFD method to investigate the permeation rate of gas mixtures. Two snapshots of the simulated systems containing silicon carbide nanosheets, methane and hydrogen sulfide gases (yellow: silicon; green: carbon; white: hydrogen and purple: sulfur). Silicon and Carbon atoms are displayed with van der Waals modes. [Display omitted]